2021
DOI: 10.1177/00469580211065684
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of the Profiles of 12 Sexually Transmitted Disease Pathogens in the Republic of Korea in 2019

Abstract: Background: Sexually transmitted diseases (STDs) are common infectious diseases in humans transmitted through unprotected sexual activities. In South Korea, despite the high annual incidence of STDs, detailed examinations of pathogen-specific factors and causes for delays in diagnosis and treatment are still lacking. Furthermore, STD prevalence patterns and important pathogen-specific factors remain unclear. Herein, we retrospectively analyzed the epidemiology of STDs in South Korea in 2019 by analyzing the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The analysis of 10 years’ data in this study shows that the rate of coinfection among male STI patients with bacterial STI in Hong Kong has tripled from 5% in 2009 to 15% in 2019. Worldwide, the percentage of STI coinfection among males has shown high variability between countries, with 47% in South Korea [8], 40% in India [4], 21% in Australia [5], 14% in Portugal [6], and 7% in the Netherlands [7]. The variation might have arisen from differences in the forms of STI investigated and definitions adopted for coinfection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of 10 years’ data in this study shows that the rate of coinfection among male STI patients with bacterial STI in Hong Kong has tripled from 5% in 2009 to 15% in 2019. Worldwide, the percentage of STI coinfection among males has shown high variability between countries, with 47% in South Korea [8], 40% in India [4], 21% in Australia [5], 14% in Portugal [6], and 7% in the Netherlands [7]. The variation might have arisen from differences in the forms of STI investigated and definitions adopted for coinfection.…”
Section: Discussionmentioning
confidence: 99%
“…variability between countries, with 47% in South Korea [8], 40% in India [4], 21% in Australia [5], 14% in Portugal [6], and 7% in the Netherlands [7]. The variation might have arisen from differences in the forms of STI investigated and definitions adopted for coinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It binds to the downstream Y1 receptor and regulates bone homeostasis (48). Park et al (49) found reduced HSC numbers in the bone marrow of NPY-deficient mice, which might be explained by injury of sympathetic nerve fibers. Sousa et al (50) demonstrated that deletion of the Y1 receptor negatively affects bone-resorbing activity.…”
Section: Neuropeptide Ymentioning
confidence: 99%